Investigating the role of learning mentors in primary schools - Butterfield, Jean (2012)
This thesis is the result of an investigation into the use of the learning mentor support mechanism in primary schools in England. Learning mentoring is designed to reduce barriers to learning in individual children. This research was devised to enhance current knowledge of the learning mentor process and practices, and the impact of mentoring programmes on pupils.